PENGARUH LATIHAN INTERVAL TRAINING 220 YARD TERHADAP DAYA TAHAN VO2MAX ATLET TAEKWONDO BADNUR MEDISA CLUB PEKANBARU - Rahmaamalia Rahmaamalia; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was conducted to determine whether there is any influence of training interval training on the endurance of Vo2Max at Taekwondo Badnur Medisa Club Pekanbaru athlete, so that when doing the exercises or match with maximum and have good endurance. The problem in this study is the lack of endurance of Vo2Max during routine and matching exercises. Based on these problems the authors provide the form of training interval training. This type of research is experimental with one group pretest-posttest design research. The population in this research is Taekwondo Badnur Medisa Club Pekanbaru atlet which amounted to 4 people. The sampling technique used is total sampling, where the entire population of 4 people sampled. With the test run test balke 15 minutes ago conducted descriptive analysis and normality test using liliefors test at significant level α (0.05) from pretest data balke 15 minutes to produce Lo max 0.1814 smaller than Ltabel 0.381. Further training was given 16 training intervals. Then dialakukan done posttest balke 15 minutes to produce Lo max 0.262 smaller than Ltabel 0,381. From t test analysis yield Thitung equal to 10,52 and Ttabel equal to 2,132 mean Thitung > Ttabel. It can be concluded that the training interval training had an effect on the result of increased endurance of Vo2Max athlete Taekwondo Badnur Medisa Club Pekanbaru.Keywords: Interval Training, Vo2Max Endurance